2017
DOI: 10.1016/s1473-3099(17)30313-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the rVSV∆G-ZEBOV-GP Ebola virus vaccine candidate in healthy adults: a phase 1b randomised, multicentre, double-blind, placebo-controlled, dose-response study

Abstract: SummaryBackground The 2014 Zaire Ebola virus outbreak highlighted the need for a safe, effective vaccine with a rapid onset of protection. We report the safety and immunogenicity of the recombinant vesicular stomatitis virus-Zaire Ebola virus envelope glycoprotein vaccine (rVSV∆G-ZEBOV-GP) across a 6 log 10 dose range in two sequential cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 27 publications
(56 reference statements)
6
120
2
4
Order By: Relevance
“…7 The incidence of arthritis in the other phase 1, 2, and 3 trials of rVSV-ZEBOV has been lower (<5%) across a large dose range, including doses of 1 × 10⁸ pfu or higher. 2,7,8,10,11,29 A multivariate analysis indicated female sex (OR 2·2, 95% CI 1·1–4·1) and a medical history of arthritis (2·8, 1·3–6·2) as risk factors for the development of arthritis post vaccination. This analysis was done on results from a study conducted in the USA, Spain, and Canada with 1197 participants, 7 and the analysis is now mentioned in the investigator’s brochure of the rVSV-ZEBOV vaccine.…”
mentioning
confidence: 99%
“…7 The incidence of arthritis in the other phase 1, 2, and 3 trials of rVSV-ZEBOV has been lower (<5%) across a large dose range, including doses of 1 × 10⁸ pfu or higher. 2,7,8,10,11,29 A multivariate analysis indicated female sex (OR 2·2, 95% CI 1·1–4·1) and a medical history of arthritis (2·8, 1·3–6·2) as risk factors for the development of arthritis post vaccination. This analysis was done on results from a study conducted in the USA, Spain, and Canada with 1197 participants, 7 and the analysis is now mentioned in the investigator’s brochure of the rVSV-ZEBOV vaccine.…”
mentioning
confidence: 99%
“…Current vaccine candidates may also not provide the long-term protective immunity (≥10 years) necessary for sustainable protection against spillover events from animal reservoirs. Two studies reported immune responses 12 months after vaccination with different Ebola virus vaccine candidates (34,35). One of them described seroconversion in >90% of individuals after a single injection of rVSV-ZEBOV, a vesicular stomatitis virus-based Ebola virus vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Second, despite replicating to high titres in several cell lines, as a negative-sense RNA virus, rescue of recombinant VSV from plasmid DNA can be cumbersome-requiring co-transfection of five plasmids into a permissive cell line [90,91]. Finally, the reactogenicity of VSV-vectored vaccines may pose a concern; in phase I trials of VSVΔG/EBOVGP, high incidence of fever, headache, chills, fatigue, and myalgia was observed after immunisation [92,93].…”
Section: Vesicular Stomatitis Virus Vector Platformmentioning
confidence: 99%